Equilibrium and non-equilibrium clumped isotope signatures in microbially-produced H2 - Noam Lotem; Elliott P. Mueller; Jared R. Leadbetter; Nami Kitchen; Itay Halevy; John M. Eiler (Geochimica et Cosmochimica Acta, 2026)

Repeatability of commercially available visible and near infrared proximal soil sensors - Lance S. Conway; Kenneth A. Sudduth; Newell R. Kitchen; Stephen H. Anderson (Precision Agriculture, 2023)

Developing an image processing pipeline to improve the position accuracy of single UAV images - Aijing Feng; Chin Nee Vong; Jing Zhou; Lance S. Conway; Jianfeng Zhou; Earl D. Vories; Kenneth A. Sudduth; Newell R. Kitchen (Computers and Electronics in Agriculture, 2023)

Food Web Connectivity in a Mangrove–Seagrass–Patch Reef (MSP) Seascape: Lessons from a Tropical Back-Reef in Puerto Rico - Antonietta Quigg; R. J. David Wells; Jay R. Rooker; Ronald L. Hill; Larissa L. Kitchens; Michael A. Dance; David L. Moulton; Phillip J. Sanchez; Beatrice Padovani Ferreira (Fishes, 2023)
Alterations to the functions and connectivity of mangrove–seagrass–patch reef (MSP) seascapes have the potential to impact the survival, foraging activities, and movement of reef-dependent invertebrates (e.g., crabs and shrimp) and fishes. In the current study, we examined carbon flow in the Guánica Biosphere Reserve in southwestern Puerto Rico using pigment analysis of particulate organic matter and stable isotope analysis of carbon (δ13C) and nitrogen (δ15N) in flora and fauna. Several lines of evidence pointed to N2 fixers (cyanobacteria) being important for fueling primary productivity in this oligotrophic ecosystem including low (

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Report from the conference, ‘identifying obstacles to applying big data in agriculture’ - Emma L. White; J. Alex Thomasson; Brent Auvermann; Newell R. Kitchen; Leland Sandy Pierson; Dana Porter; Craig Baillie; Hendrik Hamann; Gerrit Hoogenboom; Todd Janzen; Rajiv Khosla; James Lowenberg-DeBoer; et al. (Precision Agriculture, 2021)

Adaptation of reach action to a novel force-field is not predicted by acuity of dynamic proprioception in either older or younger adults - Nick M. Kitchen; R. Chris Miall (Experimental Brain Research, 2021)
Healthy ageing involves degeneration of the neuromuscular system which impacts movement control and proprioception. Yet the relationship between these sensory and motor deficits in upper limb reaching has not been examined in detail. Recently, we reported that age-related proprioceptive deficits were unrelated to accuracy in rapid arm movements, but whether this applied in motor tasks more heavily dependent on proprioceptive feedback was not clear. To address this, we have tested groups of younger and older adults on a force-field adaptation task under either full or limited visual feedback conditions and examined how performance was related to dynamic proprioceptive acuity. Adaptive performance was similar between the age groups, regardless of visual feedback condition, although older adults showed increased after-effects. Physically inactive individuals made larger systematic (but not variable) proprioceptive errors, irrespective of age. However, dynamic proprioceptive acuity was unrelated to adaptation and there was no consistent evidence of proprioceptive recalibration with adaptation to the force-field for any group. Finally, in spite of clear age-dependent loss of spatial working memory capacity, we found no relationship between memory capacity and adaptive performance or proprioceptive acuity. Thus, non-clinical levels of deficit in dynamic proprioception, due to age or physical inactivity, do not affect force-field adaptation, even under conditions of limited visual feedback that might require greater proprioceptive control.

An individual’s propensity to disperse is dependent on the behavioral type of its peers but not its own behavioral type - Anthony J. Kitchen; David R. Chalcraft (Oecologia, 2020)

A protocol for monitoring plant responses to changing nitrogen deposition regimes in Alberta bogs - Dale H. Vitt; Melissa House; Samantha Kitchen; R. Kelman Wieder (Environmental Monitoring and Assessment, 2020)
Bogs are nutrient poor, acidic ecosystems that receive their water and nutrients entirely from precipitation (= ombrogenous) and as a result are sensitive to nutrient loading from atmospheric sources. Bogs occur frequently on the northern Alberta landscape, estimated to cover 6% of the Athabasca Oil Sands Area. As a result of oil sand extraction and processing, emissions of nitrogen (N) and sulfur (S) to the atmosphere have led to increasing N and S deposition that have the potential to alter the structure and function of these traditionally nutrient-poor ecosystems. At present, no detailed protocol is available for monitoring potential change of these sensitive ecosystems. We propose a user-friendly protocol that will monitor potential plant and lichen responses to future environmental inputs of nutrients and provide a structured means for collecting annual data. The protocol centers on measurement of five key plant/lichen attributes, including changes in (1) plant abundances, (2) dominant shrub annual growth and primary production, (3) lichen health estimated through chlorophyll/phaeophytin concentrations, (4) Sphagnum annual growth and production, and (5) annual growth of the dominant tree species ( Picea mariana ). We placed five permanent plots in each of six bogs located at different distances from the center of oil sand extraction and sampled these for 2 years (2018 and 2019). We compared line intercept with point intercept plant assessments using NMDS ordination, concluding that both methods provide comparable data. These data indicated that each of our six bog sites differ in key species abundances. Structural differences were apparent for the six sites between years. These differences were mostly driven by changes in Vaccinium oxycoccos , not the dominant shrubs. We developed allometric growth equations for the dominant two shrubs ( Rhododendron groenlandicum and Chamaedaphne calyculata ). Equations developed for each of the six sites produced growth values that were not different from one another nor from one developed using data from all sites. Annual growth of R. groenlandicum differed between sites, but not years, whereas growth of C. calyculata differed between the 2 years with more growth in 2018 compared with 2019. In comparison, Sphagnum plant density and stem bulk density both had strong site differences, with stem mass density higher in 2019. When combined, annual production of S. fuscum was greater in 2019 at three sites and not different at three of the sites. Chlorophyll and phaeophytin concentrations from the epiphytic lichen Evernia mesomorpha also differed between sites and years. This protocol for field assessments of five key plant/lichen response variables indicated that both site and year are factors that must be accounted for in future assessments. A portion of the site variation was related to patterns of N and S deposition.

A long-term precision agriculture system sustains grain profitability - M. A. Yost; N. R. Kitchen; K. A. Sudduth; R. E. Massey; E. J. Sadler; S. T. Drummond; M. R. Volkmann (Precision Agriculture, 2019)

Public–private collaboration toward research, education and innovation opportunities in precision agriculture - M. A. Yost; K. A. Sudduth; C. L. Walthall; N. R. Kitchen (Precision Agriculture, 2019)

Proprioceptive deficits in inactive older adults are not reflected in fast targeted reaching movements - Nick M. Kitchen; R. Chris Miall (Experimental Brain Research, 2019)

Field variability and vulnerability index to identify regional precision agriculture opportunity - Christopher W. Bobryk; Matt A. Yost; Newell R. Kitchen (Precision Agriculture, 2018)

Proprioceptive loss and the perception, control and learning of arm movements in humans: evidence from sensory neuronopathy - R. Chris Miall; Nick M. Kitchen; Se-Ho Nam; Hannah Lefumat; Alix G. Renault; Kristin Ørstavik; Jonathan D. Cole; Fabrice R. Sarlegna (Experimental Brain Research, 2018)

Miscanthus × Giganteus Growth and Nutrient Export on 22 Producer Fields - Matt A. Yost; Newell R. Kitchen; Kenneth A. Sudduth; Eric Allphin (BioEnergy Research, 2018)

Abundance and habitat associations of tuna larvae in the surface water of the Gulf of Mexico - Maëlle Cornic; Brad L. Smith; Larissa L. Kitchens; Jaime R. Alvarado Bremer; Jay R. Rooker (Hydrobiologia, 2018)

Long-term impact of a precision agriculture system on grain crop production - M. A. Yost; N. R. Kitchen; K. A. Sudduth; E. J. Sadler; S. T. Drummond; M. R. Volkmann (Precision Agriculture, 2017)

Occurrence of invasive lionfish (Pterois volitans) larvae in the northern Gulf of Mexico: characterization of dispersal pathways and spawning areas - L. L. Kitchens; C. B. Paris; A. C. Vaz; J. G. Ditty; M. Cornic; J. H. Cowan; J. R. Rooker (Biological Invasions, 2017)

Topsoil Thickness Influences Nitrogen Management of Switchgrass - Matt A. Yost; Newell R. Kitchen; Kenneth A. Sudduth; Allen L. Thompson; Eric Allphin (BioEnergy Research, 2017)

Habitat associations of dolphinfish larvae in the Gulf of Mexico - Larissa L. Kitchens; Jay R. Rooker (Fisheries Oceanography, 2014)
The aim of this study was to investigate the role of the northern Gulf of Mexico (Gulf) as essential habitat of common dolphinfish ( Coryphaena hippurus ) and pompano dolphinfish ( C. equiselis ) during early life and to characterize conditions in which they were found. Eight ichthyoplankton surveys were conducted during the summer months from 2007 to 2010 in northern Gulf waters off Texas and Louisiana (26–28°N, 87–93°W), during which 1145 dolphinfish larvae were collected. C. hippurus , the dominant dolphinfish species, were collected in 57% of sampling sites with an overall mean density of 0.73 larvae 1000 m −3 , whereas C. equiselis were only collected at 18% of sites with a mean density of 0.12 larvae 1000 m −3 . Generalized additive models ( GAM s) were used to examine the relationship between several environmental parameters and C. hippurus presence/absence and density. Both presence/absence and density GAM s indicated that catches of C. hippuru s larvae increased near fronts and eddies and that increased abundances were most strongly associated with higher salinities and cooler temperatures. In addition, our models showed that C. hippurus larvae were positively associated with C. equiselis larvae, suggesting that C. hippurus and C. equiselis use similar habitats. Results of this study indicate that the Gulf may represent important spawning and/or nursery habitat of dolphinfishes and that mesoscale features and physicochemical conditions influence the distribution and abundance of C. hippurus larvae in this region.

Male baboon responses to experimental manipulations of loud “wahoo calls”: testing an honest signal of fighting ability - D. M. Kitchen; D. L. Cheney; A. L. Engh; J. Fischer; L. R. Moscovice; R. M. Seyfarth (Behavioral Ecology and Sociobiology, 2013)

Within-field nitrogen response in corn related to aerial photograph color - J. D. Williams; N. R. Kitchen; P. C. Scharf; W. E. Stevens (Precision Agriculture, 2010)

Bayesian analysis of within-field variability of corn yield using a spatial hierarchical model - Pingping Jiang; Zhuoqiong He; Newell R. Kitchen; Kenneth A. Sudduth (Precision Agriculture, 2009)

Two classification methods for developing and interpreting productivity zones using site properties - Nicolás Martín; Germán Bollero; Newell R. Kitchen; Alexandra N. Kravchenko; Ken Sudduth; William J. Wiebold; Don Bullock (Plant and Soil, 2006)

From “Snakebites in the new millennium: A state-of-the-art symposium” - J. Audi; S. A. Seifert; J. F. Gennaro; J. W. Skimming; L. H. S. Van Mierop; C. S. Kitchens; M. D. Cardwell; S. P. Bush; R. T. Clark; E. A. Dugan; R. C. Dart; S. R. Rose; et al. (Journal of Medical Toxicology, 2006)

Use of a reciprocal transplant study to measure the rate of plant community change in a tidal marsh along a salinity gradient - Paul R. Wetzel; Wiley M. Kitchens; Janell M. Brush; Marsha L. Dusek (Wetlands, 2004)

Factors Affecting Reproduction and Mortality Among Baboons in the Okavango Delta, Botswana - D. L. Cheney; R. M. Seyfarth; J. Fischer; J. Beehner; T. Bergman; S. E. Johnson; D. M. Kitchen; R. A Palombit; D. Rendall; J. B. Silk (International Journal of Primatology, 2004)

Economic and Environmental Evaluation of Variable Rate Nitrogen and Lime Application for Claypan Soil Fields - Dechun Wang; Tony Prato; Zeyuan Qiu; Newell R. Kitchen; Kenneth A. Sudduth (Precision Agriculture, 2003)

Educational Needs of Precision Agriculture - N. R. Kitchen; C. J. Snyder; D. W. Franzen; W. J. Wiebold (Precision Agriculture, 2002)

Conserving Britain's biodiversity. I:Thlaspi perfoliatum L. (Brassicaceae), Cotswold Pennycress - T. C. G. Rich; C. R. Lambrick; C. Kitchen; M. A. R. Kitchen (Biodiversity and Conservation, 1998)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Spartan Pearl: A widely adapted, high yielding white skin potato cultivar - D. S. Douches; R. W. Chase; G. H. Silva; R. Hammerschmidt; N. R. Thompson; R. B. Kitchen (American Journal of Potato Research, 1992)

Michigold: A yellow-fleshed potato cultivar for fresh market - R. W. Chase; N. R. Thompson; R. B. Kitchen; G. H. Silva; R. Hammerschmidt; D. S. Douches (American Journal of Potato Research, 1992)

Irrigation, nitrogen and gypsum effects on specific gravity and internal defects of Atlantic potatoes - G. H. Silva; R. W. Chase; R. Hammerschmidt; M. L. Vitosh; R. B. Kitchen (American Journal of Potato Research, 1991)

Pre-cutting of seed potatoes - R. W. Chase; G. H. Silva; R. B. Kitchen (American Journal of Potato Research, 1989)

Saginaw Gold: A yellow-fleshed potato cultivar with medium-high specific gravity and excellent chip and french fry quality after storage - R. Coffin; R. Chase; N. Thompson; G. Johnston; A. McKeown; M. K. Keenan; D. Craven; R. Kitchen; J. Wilson; R. Y. Yada (American Journal of Potato Research, 1989)

Plot harvester for potatoes - R. W. Chase; N. R. Thompson; R. L. Ledebuhr; C. M. Hansen; R. B. Kitchen (American Journal of Potato Research, 1978)